Analisis Peran Sertifikasi Halal Pada Bisnis UMKM Kabupaten Bekasi - Camelia, Ica; Achmad, Listian Indiyani; Ainulyaqin, MH; Edy, S (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze the role of halal certification in developing MSME businesses in Bekasi Regency. Halal certification can provide consumer confidence, access to global markets, legal compliance, product differentiation and social work opportunities for MSME. This research aims to determine the role of halal certification in developing MSME businesses in Bekasi Regency and the factors that influence it. It is hoped that this research will provide theoretical and practical benefits for researchers, MSME entrepreneurs and MSME consumers in Bekasi Regency. Halal certification has an important role in the food and beverage industry, and can increase the reputation and sales of MSME. Compliance with halal standards can have a positive impact on consumer sales, market growth, access to international markets, and differentiation from competitors. The research method used in this journal is qualitative research with field research and library research designs. Data was collected through interviews, observation and documentation. The data analysis process was carried out using qualitative analysis methods, including data reduction, data display, data verification, thematic analysis and grounded theory. The research was conducted in Bekasi Regency with a focus on analyzing the role of halal certification in MSME. The results of this literature review show that the implementation of halal certification has a significant impact on the development of MSME.